2012
DOI: 10.1590/s0103-84782012000600013
|View full text |Cite
|
Sign up to set email alerts
|

Fatores prognósticos e preditivos dos tumores caninos definidos com auxílio da imuno-histoquímica

Abstract: A imuno-histoquímica pode ser aplicada na oncologia veterinária para a definição do imunofenótipo neoplásico, com possibilidades ilimitadas de utilização. A técnica baseia-se na identificação de antígenos "in situ", que podem apresentar valor prognóstico e terapêutico. A expressão de receptores de estrógeno e progesterona está diretamente relacionada ao melhor prognóstico para os neoplasmas mamários, enquanto a super-expressão do receptor KIT (CD117), proteínas Ki-67 (MIB-1), VEGF, CD31 e COX-2 podem ser assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
8

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 36 publications
0
9
0
8
Order By: Relevance
“…The determination of the immunophenotype of lymphoma is of undeniable importance, since it allows detailed diagnosis and prognosis and directs the choice of a more appropriate treatment (Horta et al 2012). In a study by Kiupel et al (1999) using the same antibodies from the present study, it was demonstrated that the determination of the immunophenotype in dogs with lymphoma was important for the prognosis of survival, indicating that dogs with B-cell lymphomas, which are less aggressive, were those with a longer survival time (Teske et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The determination of the immunophenotype of lymphoma is of undeniable importance, since it allows detailed diagnosis and prognosis and directs the choice of a more appropriate treatment (Horta et al 2012). In a study by Kiupel et al (1999) using the same antibodies from the present study, it was demonstrated that the determination of the immunophenotype in dogs with lymphoma was important for the prognosis of survival, indicating that dogs with B-cell lymphomas, which are less aggressive, were those with a longer survival time (Teske et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the occurrence of mammary neoplasia in domestic animals is a subject addressed worldwide (Lana et al 2007, Szczubial et al 2012, Gundim et al 2016, Dolka et al 2018, Marconato et al 2019. In addition, cancer is the leading cause of death in elderly dogs and the second largest cause in companion animals (Horta et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The use of the cell block technique to determine the expression of oestrogen (ER), progesterone (PR) and cytokeratin 5 (CK5) receptors allows a better therapeutic approach (Bueno y col 2013, Zanoni et al 2012Horta et al 2012). An increased expression for the oestrogen (ER) and progesterone (PR) receptors is related to a better prognosis while the positivity of the CK5 receptor is related to a worse prognosis, in both canines and humans with mammary carcinomas (Terra et al 2012, Horta et al 2012, Figueiroa et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…An increased expression for the oestrogen (ER) and progesterone (PR) receptors is related to a better prognosis while the positivity of the CK5 receptor is related to a worse prognosis, in both canines and humans with mammary carcinomas (Terra et al 2012, Horta et al 2012, Figueiroa et al 2012. In canines, the expression of ER is higher in benignant tumors than in malignant ones and is also higher in complex and mixed tumors in comparison with simple sub-types (De Las Mulas et al 2004).…”
Section: Introductionmentioning
confidence: 99%